2010
DOI: 10.1016/j.ajog.2010.06.060
|View full text |Cite
|
Sign up to set email alerts
|

Preimplantation factor promotes first trimester trophoblast invasion

Abstract: Objectives-Preimplantation factor (PIF) is a novel embryo-derived peptide which influences key processes in early pregnancy implantation, including immunity, adhesion, remodeling and apoptosis. Herein, we explore the effects of synthetic PIF (sPIF) on trophoblast invasion.Methods-Invasion patterns of immortalized cultured HTR-8 trophoblast cells were analyzed through Matrigel extracellular matrix +/− sPIF (25-100nM) in a transwell assay. Effects were compared with epidermal growth factor (EGF) 10μg/mL, scrambl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 15 publications
2
61
0
1
Order By: Relevance
“…The presence of PIF in the maternal circulation has been correlated with live births in murine and bovine models (2)(3)(4). Despite the longstanding understanding that PIF is involved in promoting maternal immune tolerance and embryo implantation (2,(5)(6)(7)(8), the mechanism by which PIF does so has remained poorly understood. Recently, a synthetic PIF analog (sPIF) of 15 amino acids (MVRIKPGSANKPSDD) was reported to elicit neuroprotective effects in a murine model of experimental autoimmune encephalomyelitis (9).…”
mentioning
confidence: 99%
“…The presence of PIF in the maternal circulation has been correlated with live births in murine and bovine models (2)(3)(4). Despite the longstanding understanding that PIF is involved in promoting maternal immune tolerance and embryo implantation (2,(5)(6)(7)(8), the mechanism by which PIF does so has remained poorly understood. Recently, a synthetic PIF analog (sPIF) of 15 amino acids (MVRIKPGSANKPSDD) was reported to elicit neuroprotective effects in a murine model of experimental autoimmune encephalomyelitis (9).…”
mentioning
confidence: 99%
“…In vitro cell invasion assay showed that, under the induction of chemotactic agent, EVT went through Matrigel from serum-free upper chamber into the lower chamber containing serum. The number of cells penetrating the membrane can reflect the invasive capability of EVT [14] . Our study confirmed that, c-erbB-2, MMP-2 and MMP-9 proteins were all expressed in EVT and as compared with the control group, the expression levels of c-erbB-2, MMP-2 and MMP-9 proteins in HCMV group were significantly lower and the activity of MMP-2 and MMP-9 was significantly decreased and the number of cells going through the member was significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Der Präimplantationsfaktor PIF, ein Protein aus 15 Aminosäuren, wird darüber hinaus nur von lebensfähigen Embryonen sezerniert und verstärkt neben der parakrinen Beeinflussung des Endometriums die Invasionsfähigkeit des Trophoblasten. PIF gilt somit als vielversprechender Marker für die embryonale Kompetenz [14,15]. Ebenso fand sich eine vermehrte Leptin-und Ubiquitinsekretion von intakten Blastozysten [16], während Faktoren, wie CXCL13 (c-x-c motif chemokine 13), SCF ("stem cell factor") und MSP-a ("macrophage stimulating protein a ") verstärkt von diesen verbraucht wurden.…”
Section: Nichtinvasives Embryoscreeningunclassified